2018
DOI: 10.1038/mi.2017.53
|View full text |Cite
|
Sign up to set email alerts
|

IL-17-driven intestinal fibrosis is inhibited by Itch-mediated ubiquitination of HIC-5

Abstract: Intestinal fibrosis is a major complication in inflammatory bowel diseases, but the regulatory mechanism that inhibits fibrosis remains unclear. Here we demonstrate that Itchmyofibroblasts express increased amounts of profibrotic collagen type I and α-SMA in response to IL-17. Mechanistically, we demonstrate that Itch directly binds to HIC-5 and targets it for K63-linked ubiquitination to inhibit IL-17-driven intestinal fibrosis. Reconstitution of Itch myofibroblasts with wild-type Itch but not the Itch-C830A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…It was later revealed that high levels of IL‐17 contributed to the spontaneous GI inflammation that occurred in Itch‐deficient mice. This GI inflammation resembled inflammatory bowel disease and was accompanied by colonic fibrosis 18,19 . Consistent with this, mice lacking the Itch activator Ndfip1 also develop severe IL‐17‐mediated GI inflammation, supporting that active Itch is required to prevent intestinal disease in mice 20 .…”
Section: Itch‐deficient Mice Show Altered T Cell Responses and Inflamsupporting
confidence: 56%
See 1 more Smart Citation
“…It was later revealed that high levels of IL‐17 contributed to the spontaneous GI inflammation that occurred in Itch‐deficient mice. This GI inflammation resembled inflammatory bowel disease and was accompanied by colonic fibrosis 18,19 . Consistent with this, mice lacking the Itch activator Ndfip1 also develop severe IL‐17‐mediated GI inflammation, supporting that active Itch is required to prevent intestinal disease in mice 20 .…”
Section: Itch‐deficient Mice Show Altered T Cell Responses and Inflamsupporting
confidence: 56%
“…Supporting this, Itch‐deficient Th17 cells give rise to more pathogenic Th17 cells that drive colitis 18,36 . Exacerbation of colitis in Itch‐deficient mice can also be due to excessive IL‐17 responsiveness, as it has been reported that Itch‐deficient myofibroblasts showed increased sensitivity to IL‐17 signaling, resulting in increased fibrosis 19 . Thus, both the lung and GI aspects of Itch deficiency are the consequence of an interplay between the dysregulated innate and adaptive immune cells…”
Section: Itch Regulation Of T Cell Fatementioning
confidence: 93%
“…28 The level of IL-17 is elevated in the intestine of IBD patients, where the cytokine facilitates intestinal fibrosis. 24,29 Likewise, IL-23 induced-expression of IL-22 is observed in psoriasis, 30 rheumatoid arthritis, 31 and IBD. 32,33 CX3Cr1 + mononuclear phagocytes promote the production of IL-22 from ILC3 cells via IL-23.…”
Section: Introductionmentioning
confidence: 99%
“…During tissue injury with a chemical, mechanical and infection condition, an inflammatory response triggers the tissue repair process. However, a dysregulated and pathological inflammatory response leads to developing scarring or a fibrotic reaction, which could impair the tissue repair function 9,18,19 . Here, we show the procedure for the TNBS-induced fibrosis animal model, which significantly shares pathophysiology with human Crohn's disease.…”
Section: Discussionmentioning
confidence: 99%